Male Fertility Patterns and Determinants - Zhang, Li.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
This book discusses the biological, methodological and sociological issues that have caused men to be overlooked in demographic and sociological literature of fertility. It explores the patterns and determinants of male fertility and studies male fertility rates as compared to those of females in 43 countries and places, over time. Data used in the aggregate level analysis come from multiple sources, including the 2001 United Nations Demographic Yearbook, the 1964 to 2004 Taiwan-Fukien Demographic Yearbooks, and National Statistics Reports by the Statistics Bureau of Republic of China. To explore male fertility determinants, the book analyzes individual data from the 2002 National Survey of Family Growth (NSFG) in the United States. The findings presented here demonstrate that male fertility differs from female fertility in both rates and determinants, which suggests that female fertility cannot fully represent human fertility.
Part 1: Introduction -- Chapter 1: Introduction and Overview -- Chapter 2. Review of Male Fertility Literature -- Chapter 3. Data and Methods -- Part II: Male and Female Fertility Differentials in Rates -- Chapter 4. A Cross-Sectional Analysis of Male and Female Fertility in 43 Countries and Places -- 1990-98 -- Chapter 5. Male and Female Fertility in Taiwan: Trends and Transitions 1949-2004 -- Part III: Male and Female Fertility Differentials in Determinants -- Chapter 6. Demographic -- Socioeconomic Characteristics and Male and Female Fertility -- Chapter 7. Religion -- Religiosity and Male and Female Fertility -- Chapter 8. The Influence of Cohabitation on Male and Female Fertility -- Chapter 9. Cultural Inheritance and Male and Female Fertility -- Conclusion.
Keywords: Social sciences; Demography; Developmental psychology; Social Sciences; Demography; Sociology, general; Gender Studies